2020
DOI: 10.1007/s11069-020-03871-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, numerical and field study investigating a heritage structure collapse after the 2015 Gorkha earthquake

Abstract: This paper presents an investigation of the collapse of a 325-year-old multi-tiered heritage temple during the 2015 Gorkha earthquake in Kathmandu, Nepal. The research comprises a reconnaissance survey followed by a geotechnical investigation and numerical back-analysis carried out to understand the potential causes of the collapse. The assessment of the structural configuration of the temple indicated seismic vulnerability in the design due to the presence of discontinuous columns over the height of the templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Kumar et al (2019) reported the damaged pattern of heritage structures within World heritage sites of Kathmandu during 2015 Gorkha Earthquake and stated the age-related deterioration and out-of-plane collapse of masonry wall were the main reason. Kumar et al (2020) studied the collapse of Jaisidewal temple (historical Pagoda style architecture) in Nepal during the 2015 Gorkha earthquake. The study showed that the seismic vulnerability in a 325-years-old temple arose due to deteriorating masonry wall and presence of discontinuous columns in the temple, while there was no failure in substructure i.e.…”
Section: Seismicity Of the Himachal Pradesh Region And Its Impact To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al (2019) reported the damaged pattern of heritage structures within World heritage sites of Kathmandu during 2015 Gorkha Earthquake and stated the age-related deterioration and out-of-plane collapse of masonry wall were the main reason. Kumar et al (2020) studied the collapse of Jaisidewal temple (historical Pagoda style architecture) in Nepal during the 2015 Gorkha earthquake. The study showed that the seismic vulnerability in a 325-years-old temple arose due to deteriorating masonry wall and presence of discontinuous columns in the temple, while there was no failure in substructure i.e.…”
Section: Seismicity Of the Himachal Pradesh Region And Its Impact To ...mentioning
confidence: 99%
“…It was also noted during post-survey 2015 Gorkha earthquake that some of the masonry structures which survived the1934 Great Nepal Bihar earthquake and the 2011 Sikkim-Nepal earthquake, collapsed during the 2015 Gorkha earthquake having similar structural features, lack of proper maintenance (Kumar et al 2019(Kumar et al & 2020.…”
Section: Typical Structural Configuration and Seismic Adaptationmentioning
confidence: 99%